Trends in Psychological Experiences of Athletes by Period in the Long Jump Competition - Deok-Hyeon Kim; Young-Kil Yun (Korea Institute of Sport Science, 2023)
PURPOSE This study explored psychological experiences in long jump competitions and examined the continuity of psychological experiences over time. METHODS A total of 28 adult long jumpers, 18 men and 10 women, were provided data through in-depth interviews. Data on psychological experiences were extraced through inductive content analysis, while continuity by period was analyzed by calculating the response frequency ratio using Excel. RESULTS First, the psychological experience in the long jump competition was categorized as fundamental, competition intelligence, emotional control, and communication capacity experience. Second, in long jump competitions, results showed that jumpers experienced mixed feelings of anxiety and pressure, self-confidence, and concentration in the first period; peer communication and analysis thinking were necessary in the second period; practical intelligence and pressure control were important in the third period; learning ability and creativity were crucial in the fourth period; learning ability and coach communication were applied in the fifth period; and fighting spirit and creativity were present in the sixth period. Third, the psychological experience of long jumpers by period, basicphysical strength was maintained; competition intelligence increased in the second and fourth periods; communication skills increased until the fifth period, and decreased after; while emotional control decreased. This reflects the contextual changes over time andthe change in competition records owing to that. CONCLUSIONS In the long jump competition, psychological experience changes by period and affects competition records. This study will contribute to further understanding of psychological continuity.